2016
DOI: 10.20506/rst.35.3.2572
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of honeybee viruses in different regions of China and Argentina

Abstract: Honeybees are threatened by various pathogens and parasites. More than 18 viruses have been described in honeybees and many of them have been detected in China and Argentina. In China, both Apis cerana and Apis mellifera are raised. In Argentina, beekeepers raise different ecotypes of A. mellifera: European honeybees (in both temperate and subtropical regions) and Africanised honeybees (in subtropical areas only). A thorough study was carried out in both China and Argentina to analyse the current virus presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Losses of Africanized honey bee colonies due to varroosis are not reported and possible negative effects on honey production seem to be negligible [160]. This is surprising, as in contrast to South Africa, viruses associated with Varroa like Deformed Wing Virus are widespread in South America [164][165][166] and Africanized bees are not resistant against the virus [167,168], although in one study, the rate of virus increase was lower in Africanized bees than in European bees [169].…”
Section: Resistance Of Africanized Beesmentioning
confidence: 99%
“…Losses of Africanized honey bee colonies due to varroosis are not reported and possible negative effects on honey production seem to be negligible [160]. This is surprising, as in contrast to South Africa, viruses associated with Varroa like Deformed Wing Virus are widespread in South America [164][165][166] and Africanized bees are not resistant against the virus [167,168], although in one study, the rate of virus increase was lower in Africanized bees than in European bees [169].…”
Section: Resistance Of Africanized Beesmentioning
confidence: 99%
“…ABPV infection rate of (22%) in A . c. cerana was reported in Guangdong, while there was no infection of this virus in Fujian until now (Ding et al., ). IAPV detection was reported in Fujian Province with a prevalence of (11%) in A. mellifera, and the prevalence of IAPV in A .…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, (37.5%) of A. mellifera colonies were infected with CSBV, which showed that the western honeybee is also susceptible to CSBV (Nai et al, 2018). ABPV infection rate of (22%) in A. c. cerana was reported in Guangdong, while there was no infection of this virus in Fujian until now (Ding et al, 2016). IAPV detection was reported in Fujian Province with a prevalence of (11%) in A. mellifera, and the prevalence of IAPV in A. c. cerana was also reported in…”
Section: The Surveys Of Domestic a C Cerana Populations In China Havementioning
confidence: 92%
“…In addition, previous reports demonstrated that the virus present in different bee food sources (honey, pollen and royal jelly) may be transmitted horizontally between adult bees such as queens, workers, or drones [6]. Recent studies showed the presence of virus in honeybee colonies from Argentinean producers located along temperate and subtropical regions [7][8][9]. Notably, many honeybee viruses have been detected in Argentinian stingless bees and bumblebees [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…
Centro de investigaciones en CienciasAgronómicas y Veterinarias (CICVyA), Argentina Recently, BQCV was detected in Argentinean apiaries located along different geographic regions, with a prevalence of 8% [8]. Acute bee paralysis virus (ABPV) is a widespread bee pathogen that has been linked with colony losses [14].
…”
mentioning
confidence: 99%